Customer's Loyalty of Indonesia Cellular Operators in The Pandemic of COVID-19 - Rachmawati, Indira (SBM ITB, 2020)
Abstract. The cellular operators business in Indonesia has significantly increased during pandemic of COVID-19 since the issuance of the government regulation regarding work from home and study from home. The increasing number of subscribers is getting higher along with the increasing high churn rate. The intention of the study was to determine the potential predictors of customer's loyalty to cellular operators. The findings show, First, user experience directly influences loyalty. Second, corporate image is revealed to strengthen the effect of user experience on switching barriers and subsequent impact on loyalty, which indicates that a good corporate image can increase customer loyalty. Third, satisfaction and switching barriers mediate the relationship between user experience and loyalty. This implies that if users perceive a good experience with their operators, they will satisfied and loyal to the current operator. In line with this situation, if there are too many barriers to switch to other operators and they believe getting value for money, they will remain loyal. The conceptual research framework proposed can be differentiated between users who perceived corporate image is high and those who perceived corporate image is low; they can be differentiated between pre-paid and post-paid cellular users. The contribution of this study lies in the fact that the path between the five dimensions of user experience to loyalty of cellular operator, the combination with the mediator of satisfaction and switching barrier to loyalty, the moderating role of corporate image which affects the direction and strengthen the relationship between user experience and switching barriers.Keywords: Cellular operators, corporate image, COVID-19, loyalty, user experienceAbstract. Bisnis operator seluler di Indonesia mengalami peningkatan yang signifikan selama pandemi COVID-19 sejak dikeluarkannya peraturan pemerintah tentang bekerja dari rumah dan belajar dari rumah. Jumlah pelanggan yang semakin meningkat seiring dengan churn rate yang semakin tinggi. Tujuan dari penelitian ini adalah untuk menentukan prediktor potensial dari loyalitas pelanggan kepada operator seluler. Temuan menunjukkan, Pertama, pengalaman pengguna secara langsung memengaruhi loyalitas. Kedua, pengungkapan citra perusahaan untuk memperkuat pengaruh pengalaman pengguna terhadap peralihan hambatan dan dampak selanjutnya terhadap loyalitas, yang menunjukkan bahwa citra perusahaan yang baik dapat meningkatkan loyalitas pelanggan. Ketiga, kepuasan dan peralihan hambatan memediasi hubungan antara pengalaman pengguna dan loyalitas. Ini menyiratkan bahwa jika pengguna merasakan pengalaman yang baik dengan operator mereka, mereka akan puas dan setia kepada operator saat ini. Sejalan dengan situasi ini, jika ada terlalu banyak hambatan untuk beralih ke operator lain dan mereka yakin mendapatkan nilai uang, mereka akan tetap setia. Kerangka penelitian konseptual yang diusulkan dapat dibedakan antara pengguna yang mempersepsikan citra perusahaan tinggi dan yang mempersepsikan citra perusahaan rendah; mereka dapat dibedakan antara pengguna seluler prabayar dan pascabayar. Kontribusi penelitian ini terletak pada kenyataan bahwa jalur antara lima dimensi pengalaman pengguna ke loyalitas operator seluler, kombinasi dengan mediator kepuasan dan pengalihan penghalang ke loyalitas, peran moderasi citra perusahaan yang mempengaruhi arah dan memperkuat hubungan antara pengalaman pengguna dan peralihan hambatan.Kata kunci: Citra perusahaan, COVID-19, loyalitas, operator seluler, pengalaman pengguna